Fight alone or together? The influence of risk perception on helping behavior - Liping Yin; Yenchun Jim Wu (Journal of Risk and Financial Management, 2022)
Will there be a greater sense of solidarity and friendship during public crises? This study aims to determine whether risk perception influences employees' willingness to assist in times of public crisis, taking COVID-19 as a specific research scenario and based on the theory of 'tend and befriend'. This study hypothesized that risk perception will influence employees' helping behavior via the in-group identity, with the degree of impact dependent on the COVID-19 pandemic's severity. A questionnaire survey of 925 practitioners from various industries in the pandemic area revealed that: risk perception has a positive influence on employees' helping behavior; in-group identity plays a certain mediating role in the process of risk perception that influences employees' helping behavior; and the severity of a local pandemic negatively moderates the relationship between risk perception and helping behavior, but positively moderates the relationship between risk perception and in-group identity. Specifically, employees in high-risk areas are more likely to 'align' (higher degree of recognition by the in-group) but demonstrate less helping behavior, compared with those in areas with moderate and low risk from the COVID-19. By contrast, employees in low-risk areas display more helping behavior but have less in-group identity, compared with those in areas with moderate and high risk from the COVID-19. This study expands the research on the relationship between risk perception and helping behavior, enriches the research results on risk management theory, and provides a practical reference for risk governance.
Keywords: 330; COVID-19; helping behavior; in-group identity; risk perception; severity of a local pandemic